Effect of Thermo-oxidation on the local mechanical behaviour of epoxy polymer materials for high temperature applications. (October 2016) - Gigliotti, M.; Minervino, M.; Lafarie-Frenot, M.C.; Grandidier, J.C.
Highlights: Coupled experimental/numerical approach for the characterization of the effects of thermo-oxidation on the local mechanical behaviour of aged polymer materials. Experimental approach based on ultra-micro indentation (UMI) and interferometric microscopy (IM) tests. Numerical approach based on an ageing dependent nonlinear viscoelastic/softening constitutive law developed within the framework of the Thermodynamics of Irreversible Processes (TIP) with Internal Variables (TIV). The elastic parameters of the constitutive law have the tendency to increase monotonically and linearly with ageing The material exhibits less softening behavior with ageing, and, with respect to the virgin state, ageing tends to enhance the short-term viscoelastic response of the material . Abstract: This paper presents an original coupled experimental/numerical approach for the characterization of the effects of thermo-oxidation on the local mechanical behaviour of aged polymer materials. The experimental approach is based on ultra-micro indentation (UMI) and interferometric microscopy (IM) tests. The UMI load vs. displacement curve is exploited to gain some information about the material behaviour at the short-range timescales, the IM measurement of the three-dimensional indentation print and of its evolution with time allows characterizing the material behaviour at the long-range timescales. The numerical approach is based on an ageing dependent nonlinear viscoelastic/softening constitutive law developed within the framework of the Thermodynamics of Irreversible Processes (TIP) with Internal Variables (TIV). The constitutive law is integrated within a 3D ABAQUS® finite element model of the test setup and the parameters of the law are identified for different ageing conditions.